(untitled) (Swiss Medical Weekly, 2012)
BACKGROUND: In 2005, findings of the first “cost of disorders of the brain in Europe” study of the European Brain Council (EBC) showed that these costs cause a substantial economic burden to the Swiss society. In 2010 an improved update with a broader range of disorders has been analysed. This report shows the new findings for Switzerland and discusses changes. METHODS: Data are derived from the EBC 2010 census study that estimates 12-month prevalence of 12 groups of disorders of the brain and calculates costs (direct health-care costs, direct non-medical costs and indirect costs) by combining top-down and bottom up cost approaches using existing data. RESULTS: The most frequent disorder was headache (2.3 million). Anxiety disorders were found in 1 million persons and sleep disorders in 700,000 persons. Annual costs for all assessed disorders total to 14.5 billion Euro corresponding to about 1,900 EUR per inhabitant per year. Mood, psychotic disorders and dementias (appr. 2 billion EUR each) were most costly. Costs per person were highest for neurological/neurosurgery-relevant disorders, e.g. neuromuscular disorders, brain tumour and multiple sclerosis (38,000 to 24,000 EUR). CONCLUSION: The estimates of the EBC 2010 study for Switzerland provide a basis for health care planning. Increase in size and costs compared to 2005 are mostly due to the inclusion of new disorders (e.g., sleep disorders), or the re-definition of others (e.g., headache) and to an increase in younger cohorts. We suggest coordinated research and preventive measures coordinated between governmental bodies, private health-care and pharmaceutical companies.